Some Comments on Quasi-Birth-and-Death Processes and Matrix Measures - Holger Dette; Bettina Reuther (Journal of Probability and Statistics)
We explore the relation between matrix measures and quasi-birth-and-death processes. We derive an integral representation of the transition function in terms of a matrix-valued spectral measure and corresponding orthogonal matrix polynomials. We characterize several stochastic properties of quasi-birth-and-death processes by means of this matrixmeasure and illustrate the theoretical results by several examples.